Psoriasis and comorbidities: general practitioners’ awareness - Costa-Silva, Miguel (2018)
INTRODUCTION: Systemic inflammatory diseases such as psoriasis, systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA) are associated with an increased prevalence of cardiovascular diseases (CVD) and other comorbidities. The primary aim of this study was to assess the screening practices of general practitioners (GPs) with regard to the most frequent comorbidities in patients with psoriasis. METHODS: We adapted, with permission, a questionnaire that was used by Parsi et al. in 2012, which was then distributed to GP residents and consultants. RESULTS: Overall, 372 questionnaires were collected. Significantly more physicians screen for CV risk factors in patients with RA and SLE than in patients with psoriasis. There was no statistically significant difference between GP residents in the initial and final phase of residency, or between GP residents and consultants regarding awareness of increased prevalence of CVD in psoriasis or comorbidity screening practices in psoriasis patients. CONCLUSIONS: Most GP residents and consultants that participated in this study are not aware of an increased CV risk in patients with psoriasis and assign greater importance regarding this risk to other inflammatory diseases such as RA and SLE.